2022
DOI: 10.3389/fmicb.2022.816968
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of the Lysine Acetylome in the Aquatic Animals Pathogenic Bacterium Vibrio mimicus

Abstract: Protein lysine acetylation is an evolutionarily conserved post-translational modification (PTM), which is dynamic and reversible, playing a crucial regulatory role in almost every aspect of metabolism, of both eukaryotes and prokaryotes. Several global lysine acetylome studies have been carried out in various bacteria, but thus far, there have been no reports of lysine acetylation for the commercially important aquatic animal pathogen Vibrio mimicus. In the present study, we used anti-Ac-K antibody beads to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Similarly, in the cellular component (CC) category, most of the identified lysine-acetylated and -succinylated proteins were prevalent in the cell, cell part, cytoplasm, intracellular part, and intracellular categories ( Figure 3 C). Consistent with previous research, the identified Kac proteins were enriched in metabolic processes and cell locations similar to BW25113 and V. mimicus [ 29 , 48 ]. When compared to Kac proteins, the significantly enriched categories were quite different for Ksu proteins in the molecular function (MF) category.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly, in the cellular component (CC) category, most of the identified lysine-acetylated and -succinylated proteins were prevalent in the cell, cell part, cytoplasm, intracellular part, and intracellular categories ( Figure 3 C). Consistent with previous research, the identified Kac proteins were enriched in metabolic processes and cell locations similar to BW25113 and V. mimicus [ 29 , 48 ]. When compared to Kac proteins, the significantly enriched categories were quite different for Ksu proteins in the molecular function (MF) category.…”
Section: Resultssupporting
confidence: 90%
“…The identified Ksu (692 proteins) and Kac proteins (588 proteins) accounted for 19.3% and 16.4% of the total proteins (3580) in E. tarda , respectively. When compared to the bacterial acetylome and succinylome of other animal pathogens studied, the percentage of Kac proteins was lower than those of V. alginolyticus (27.1%) [ 14 ] and A. hydrophila (24.6%) [ 16 ] but was higher than in V. parahemolyticus (13.6%) and V. mimicus (15.5%) [ 29 ]. The percentage of Ksu proteins was lower than in E. coli (23.91%) [ 30 ] but was higher than in several species of bacteria such as A. hydrophila (16.0%) [ 28 ], V. parahemolyticus (13.3%) [ 15 ], M. tuberculosis (17.07%) [ 31 ], and Pseudomonas aeruginosa (10.5%) [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The whole protein (500 μg) of V. alginolyticus under bile salt stress was incubated with specific polyclonal antibodies OmpN, OmpR, and GrpE at 4°C overnight to precipitate target proteins, as previously described ( 10 ). Briefly, the protein A/G beads were washed three times with pre-cooled PBS buffer (137 mM NaCl, 2.7 mM KCl, 4.3 mM Na 2 HPO 4 , 1.4 mM KH 2 PO 4 , pH 7.2–7.4) and then added to the lysate for incubation at 4°C for 2 h. The beads were centrifuged at 4°C and 2,500 g for 5 min to remove the supernatant, and washed five times with pre-cooled PBS buffer.…”
Section: Methodsmentioning
confidence: 99%
“…g ., glucose, re-sensitizes antibiotic-resistant bacteria to antibiotics ( 25 , 43 ). Recent studies also show that the glycolytic pathway and the pyruvate cycle are subjected to the regulation of acetylation and succinylation, indicating that protein post-translation modification may be involved in serum resistance ( 44 46 ). Actually, our previous study demonstrated that the activity of the pyruvate cycle was decreased by serum ( 17 ).…”
Section: Discussionmentioning
confidence: 99%